THE IMPORTANCE OF THE COMPLIANCE TO A MEDICAL TREATMENT OF A PATIENT WITH A VERY HIGH CARDIOVASCULAR RISK AND COMORBIDITY: ARTERIAL HYPERTENSION, ATRIAL FIBRILLATION AND DIABETES MELLITUS - Zolotarova, T. V.; Brynza, M. S.; Mehtieva, F. B. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The ultimate goal of any prescribed medical therapy is to achieve certain desired results in the patients concerned. Compliance to medical recommendations not only includes patient compliance with medication but also with diet, exercise, or lifestyle changes. Considered a clinical example of the patient of a very high cardiovascular risk with comorbid pathology: arterial hypertension, atrial fibrillation and diabetes mellitus. We have shown with this case as in comorbid patients with high cardiovascular risk could be organized medical treatment without polypharmacy.Compliance to a prescribed medication showed a positive effect in different researches. Patients with a high adherence to medication had improved the quality of life (QOL). These results in importance not only in developing intervention programs for patients but also in improving their QOL through sustainable health promotion. Avoiding of polypharmacy another main condition which increases the compliance of comorbid patients with high cardiovascular risk to medical recommenda-tions. Making sure patients understand the drug dosing regimen could also improve compliance.